Why is Policy Advocacy Important for Poor Farmers? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Mainza Mugoya from Eastern Africa Farmers' Union. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya